Contemporary Nostalgia - Salmose, Niklas (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Some of the most pressing contemporary issues (ecological crisis, migration and integration, fragmented worldviews, social media, fake news, extremist politics and terrorism) can be understood more profoundly through how they interact with both individual and collective forces of nostalgia. Nostalgia is politics, but these politics are also interwoven with media and culture. Notwithstanding how nostalgia is used or contextualized in terms of politics and social practices, commodification or personal development, its power is primarily situated within its efficacy as a governing, influential human emotion. The vast and luminous contributions to this special issue on contemporary nostalgia are all investigating the role different aesthetic media formats (film, music, literature, computer games) plays in nostalgic negotiations with style, history, migration, love, nationalism, diaspora, irony, modernity, colonial and postcolonial discourses, and adoption. Mutually, these essays stand out as important, original, critical contributions to the expanding field of nostalgia studies and offer a valued insight on our world.